2016
DOI: 10.1002/maco.201508670
|View full text |Cite
|
Sign up to set email alerts
|

Self‐healing silane coatings of cerium salt activated nanoparticles

Abstract: This work investigates the effect of cerium salt activated nanoparticles as nanoreservoirs on the self-healing properties of silane hybrid coatings deposited on electro-galvanized steel substrates. The substrates were pre-treated with 3-glycidoxypropyl-trimethoxysilane (GPTMS) and bisphenol A (BPA), modified with cerium ion-activated CeO2-ZrO2 and CeO2-SiO2 nanoparticles. The morphology of the coating before corrosion tests was examined using atomic force microscopy (AFM). The results indicate the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…After 1 h of exposure, the impedance values of coating are extremely low at the low studied frequency (i.e., 0.01 Hz) as shown in Fig. 5b due to the presence of defects that enhance the dissolution 60 . However, when the exposure periods increase, the impedance values gradually increase, and this is potentially due to the transformation and deposition of corrosion products on coating surface.…”
Section: Resultsmentioning
confidence: 98%
“…After 1 h of exposure, the impedance values of coating are extremely low at the low studied frequency (i.e., 0.01 Hz) as shown in Fig. 5b due to the presence of defects that enhance the dissolution 60 . However, when the exposure periods increase, the impedance values gradually increase, and this is potentially due to the transformation and deposition of corrosion products on coating surface.…”
Section: Resultsmentioning
confidence: 98%
“…Another important achievement in improving film growth and its corrosion performance was reported by doping silane films with nanoscaled inert particles, e.g. SiO 2 [53], CeO 2 [54,55], and TiO 2 [56,57], CeO 2 •ZrO 2 , [58], ZnO [59], Al 2 O 3 [60]. Most of the authors confirmed that the presence of the nanoparticles increases the thickness of the silane layer and contributes to the blockage of conductive pathways through the silane layer, hindering the electrolyte uptake (pore blocking effect).…”
Section: Modification Of Silane Films With Nanoparticlesmentioning
confidence: 99%
“…The literature reports that the combination of ceria nanoparticles and cerium ions [21] or silica nanoparticles and lanthanum ions [68] creates a synergistic effect that significantly improves the anticorrosive properties of silane films. The corrosion tests conducted by Zandi Zand et al [58] suggest that activated CeO 2 -ZrO 2 nanoparticles are more effective as nanostructured cerium ion reservoirs and can provide prolonged release of inhibitor ions.…”
Section: Modification Of Silane Films With Nanoparticlesmentioning
confidence: 99%
“…This is probably due to the corrosion that occurs as a result from the arrival the corrosive solution to the lead metal surface. After 96 h, the phase angle shows a stability which can be attributed to the insoluble corrosion products that might hinder the electrolyte to pass to the lead metal surface [43].…”
Section: Long Term Evaluation Of the Coatingmentioning
confidence: 99%